Effect of Health Education on Mothers’ Knowledge of Posyandu: A Pre-Post Study - Dewi; Sumarmi; Kartini H, Anita; Saputri, Citra Ayu (Omni Nursing Journal, 2025)
Background: Posyandu is a community-based health service aimed at improving maternal and child health, organized with the active participation of the community. Objective: This study aimed to assess the effectiveness of education on the benefits of Posyandu in improving the knowledge of mothers with toddlers aged 1–5 years. Methods: A one-group pretest–posttest design was used. The study population consisted of all mothers of toddlers aged 1–5 years at Posyandu Cempaka, Campagaloe Village, within the working area of Campagaloe Health Center. A total of 32 respondents were recruited using total sampling. Knowledge levels were categorized as good, sufficient, or poor, and assessed before and after the educational intervention. Data were analyzed using the Wilcoxon signed-rank test. Results: Before the intervention, 9 respondents (28.1%) had good knowledge and 23 respondents (71.9%) had sufficient knowledge. After the intervention, 18 respondents (56.2%) demonstrated good knowledge and 14 respondents (43.8%) had sufficient knowledge. Statistical analysis showed a significant improvement in knowledge scores after the intervention (p < 0.001). Conclusion: Educational sessions significantly improved mothers’ knowledge about the benefits of Posyandu. Strengthening regular health education activities by local health workers is recommended to further enhance maternal awareness and participation.